Anti-tissue transglutaminase IgA levels in severe acute malnutrition in children up to 60 months of age-a cross-sectional study from North-West India - Tulsi, Nitika; Sharma, Seema; Rehalia, Neha (International Journal of Contemporary Pediatrics, 2025)
Background: To evaluate anti-tissue transglutaminase IgA (anti-tTG IgA) levels among children suffering from severe acute malnutrition (SAM) aged up to 60 months. Methods: This observational study was conducted at Dr. Rajendra Prasad Government Medical College, Kangra at Tanda, Himachal Pradesh. A total of 100 children diagnosed with SAM, meeting the inclusion criteria, were enrolled. Following thorough clinical assessment and management as per standard protocols, their anti-tTG IgA levels were measured. Results: Elevated anti-tTG IgA levels (>4 U/ml) were observed in 37% of participants. Among them, 21% showed weakly positive results while 16% had strongly positive levels. Conclusion: Screening for celiac disease using anti-tTG IgA levels in SAM patients with persistent gastrointestinal symptoms is crucial. For children with levels exceeding 10 U/ml, further diagnostic procedures like intestinal biopsy are recommended to facilitate timely diagnosis and intervention.